The impact of oil price shocks on the military expenditure of selected MENA oil exporting countries: symmetric and asymmetric cointegration analysis - Abdlaziz, Rizgar Abdlkarim; Naseem, N. A. M.; Slesman, Ly; Ahmed, Younis Ali (University of Tehran * Faculty of Economics, 2021)
This paper examines the symmetric and asymmetric effects of oil prices on military expenditure of selected the Middle East and North Africa (MENA) oil-exporting countries. Using Linear Autoregressive Distributed Lag (ARDL) and Nonlinear Autoregressive Distributed Lag (NARDL) frameworks on annual data covers from 1960 to 2014, this paper documents that oil prices and the military expenditure shares a stable long run relationship in all cases except Algeria. The ARDL empirical findings reveal that oil price has a positive and significant effect on military spending in all cases except Tunisia. The NARDL results further reveal the existence of asymmetric pieces of evidence that the increase in oil prices increases military spending while the decrease in oil prices reduces the military spending in the long-run for Saudi Arabia, Iran, Algeria, Kuwait, and Oman. In the short run, the results demonstrate the existence of asymmetry effect of oil price on military spending only for Iran.